Evaluation of Thyroid Function Tests among Chronic Kidney Disease Patients attended at a Tertiary Care Hospital in Dhaka City (Journal of National Institute of Neurosciences Bangladesh, 2023)
Background: Serological status of thyroid hormones is important among chronic kidney disease patients.Objective: The purpose of the present study was to see the status of thyroid hormones among chronic kidney disease patients.Methodology: This cross-sectional study was done From January 2013 to December 2013 in the Department of Nephrology, Dhaka Medical College Hospital. A total of 50 diagnosed cases of adult male with different stages of CKD (CKD stage 3, 4, 5 and 5D) patients along with age-matched 51 healthy individuals were included. Serum Thyroid hormone T3 done by [1251] RIA kit, T4 done by T4 [1251] RIA kit, TSH level done by Turbo TSH [1251] IRMA kit.Result: A total number of 101 patients were recruited for this study of which 51 cases were in the group A and the rest of the 50 cases were in the group B. The mean serum T3 level was found 1.85±0.7 nmoL/L in group A and 2.79±0.55 nmoL/L in group B (p